Socioeconomic status and vitamin D deficiency among women of childbearing age: a population-based, case–control study in rural northern China. Issue 3 (22nd March 2021) - Lin, Shiqi; Jiang, Lifang; Zhang, Yuan; Chai, Jian; Li, Jiajia; Song, Xinming; Pei, Lijun
Abstract : Objective: To explore the association between socioeconomic status (SES) and vitamin D deficiency/insufficiency of women of childbearing age in rural northern China. Design: A population-based, case–control study was conducted. Setting: Four counties of Henan Province, China from 2009 to 2010. Participants: 1151 non-pregnant healthy women between 18 and 40 years old. Primary and secondary outcome measures: Serum 25-hydroxyvitamin D (25(OH)D) levels were measured using high-performance liquid chromatography-tandem mass spectrometry. Vitamin D insufficiency was defined as serum 25(OH)D ≥20 ng/mL and <30 ng/mL, deficiency as ≥10 ng/mL and <20 ng/mL, and severe deficiency as <10 ng/mL. SES was measured separately by women's and their husbands' education level and occupation, household income and expenditure, as well as aggregately by SES index constructed with principal component analysis. Results: The median serum 25(OH)D level was 20.90 (13.60–34.60) ng/mL, and the prevalence of vitamin D insufficiency, deficiency and severe deficiency was 20.16%, 31.80% and 15.99%, respectively. After adjustment, household annual income <¥10 000 was associated with increased risk of vitamin D insufficiency (adjusted OR (aOR): 2.10, 95% CI 1.41 to 3.14), deficiency (aOR: 1.58, 95% CI 1.09 to 2.29) and severe deficiency (aOR: 2.79, 95% CI 1.78 to 4.38); inadequate household income for expenditure was associated with elevated risk of vitamin D insufficiency (aOR: 1.66, 95% CI 1.08 to 2.54) and deficiency (aOR: 1.81, 95% CI 1.26 to 2.62); low SES index was associated with elevated risk of vitamin D insufficiency (aOR: 2.40, 95% CI 1.52 to 3.80) and deficiency (aOR: 1.64, 95% CI 1.08 to 2.50); and both middle and low SES index were associated with increased risk of vitamin D severe deficiency (aOR: 1.70, 95% CI 1.02 to 2.84; aOR: 2.45, 95% CI 1.45 to 4.14). Conclusions: Lower SES was associated with higher risk of vitamin D deficiency/insufficiency in women of childbearing age in rural northern China. More should be done to explore potential mechanisms and to narrow down SES inequalities in vitamin D status.